Comparative Analysis of the Determinants and Behaviour of Investment Demand between South Africa and Zimbabwe - Malumisa, Sambulo (Journal of Economics and Behavioral Studies, 2013)
The study investigates the determinants of private investment in South Africa and Zimbabwe employing annual data over the 1980-2010 periods. The influence of gross domestic product (GDP), government debt, inflation, and interest rate policies are considered. Applied vector autoregressive and error correction models are used to estimate long- and short-run relationships among variables. The results suggest that GDP has a positive effect on private investment. Government debt has a crowding out effect on private investment, and inflation is shown to negatively affect investment. Increases in interest rates discourage private investment in South Africa